Epidemiology and microbiology of nosocomial bloodstream infections: analysis of 482 cases from a retrospective surveillance study - Wu, Jian-nong (Zhejiang University Press, 2015)

(untitled) (J Zhejiang Univ Sci B)
In many traditional Chinese medicine (TCM) hospitals, most patients are elderly with chronic diseases. Nosocomial bloodstream infections (nBSIs) are an important cause of morbidity and mortality. A retrospective surveillance study was performed to examine the epidemiology and microbiology of nBSIs in a TCM hospital from 2009 to 2011. A total of 482 patients with nBSIs were included in the study period. The incidence rate was 5.7/1000 admissions. Escherichia coli (25.5%) was the most common Gram-negative and coagulase-negative staphylococcus (CoNS) (14.1%) was the most common Gram-positive organism isolated. One-third of the E. coli and Klebsiella pneumoniae isolated from the nBSIs were the third-generation cephalosporin-resistant. Half of the Acinetobacter species isolates were resistant to imipenem. Of all the CoNS isolates, 90.7% were resistant to methicillin. Carbapenems and glycopeptide were the most frequently used for nBSI therapy. Only about one-third of patients (157/482) received appropriate empirical therapy. Septic shock, hemodialysis, Pitt bacteremia score >4, urinary tract infection, and appropriate empirical therapy were most strongly associated with 28-d mortality. The incidence of nBSIs was low in the TCM hospital but the proportion of nBSIs due to antibiotic-resistant organisms was high. A high Pitt bacteremia score was one of the most important risk factors for mortality in nBSIs. Therefore, the implementation of appropriate empirical therapy is crucial to improve the clinical outcome of nBSIs.